2012
DOI: 10.1002/ejoc.201200350
|View full text |Cite
|
Sign up to set email alerts
|

Application of LB‐Phos·HBF4 in the Suzuki Coupling Reaction of 2‐Bromoalken‐3‐ols with Alkylboronic Acids

Abstract: LB‐Phos·HBF4 was used in the Suzuki coupling reaction of 2‐bromoalken‐3‐ols with alkylboronic acids to give the coupling products in moderate to good yields. Substituents such as benzyl, phenyl, allyl, and alkyl are tolerated at the 1‐ and 3‐positions of the 2‐bromoalken‐3‐ols. The reactions of both primary and secondary alkylboronic acids proceed smoothly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Next, the SMC of primary alkylboronic acids 72 with alkenyl halides 73 was reported using air-stable catalyst PdCl(C 3 H 5 )(dppb) and Cs 2 CO 3 , and toluene or xylene as solvents (Scheme 12B) [113]. In 2012, Ma et al used Pd(OAc) 2 with K 2 CO 3 and an air-stable monophosphine HBF 4 salt (L9: LB-Phos.HBF 4 ) as an efficient ligand to couple primary and secondary alkylboronic acids 75 with 2-bromoalken-3-ol derivatives 76 (Scheme 12C) [114]. In 2014, Tang et al revealed a sterically demanding aryl-alkyl SMC between di-ortho-substituted arylhalides 79 and (secondary) cycloalkylboronic acids 78 using a highly reactive Pd-AntPhos catalyst that allowed to reduce the β-hydride elimination (Scheme 12D).…”
Section: Scheme 12 Alkylboronic Acids As Coupling Partners In Sp 3 -mentioning
confidence: 99%
“…Next, the SMC of primary alkylboronic acids 72 with alkenyl halides 73 was reported using air-stable catalyst PdCl(C 3 H 5 )(dppb) and Cs 2 CO 3 , and toluene or xylene as solvents (Scheme 12B) [113]. In 2012, Ma et al used Pd(OAc) 2 with K 2 CO 3 and an air-stable monophosphine HBF 4 salt (L9: LB-Phos.HBF 4 ) as an efficient ligand to couple primary and secondary alkylboronic acids 75 with 2-bromoalken-3-ol derivatives 76 (Scheme 12C) [114]. In 2014, Tang et al revealed a sterically demanding aryl-alkyl SMC between di-ortho-substituted arylhalides 79 and (secondary) cycloalkylboronic acids 78 using a highly reactive Pd-AntPhos catalyst that allowed to reduce the β-hydride elimination (Scheme 12D).…”
Section: Scheme 12 Alkylboronic Acids As Coupling Partners In Sp 3 -mentioning
confidence: 99%
“…The dienol motif of 3 can be found as key structural components of either natural products or in key intermediates in natural product synthesis and, because of its densely packed functionalities, is rich with reactivity . As summarized in Scheme b, it can be mainly assembled in the following manners, but with limitations: i) the Suzuki–Miyaura coupling, which is straightforward but requires difficult‐to‐access chiral α‐haloallylic alcohols to prepare chiral 3 ; ii) the addition of buta‐2,3‐dien‐1‐ylmetal species to aldehydes, which are mostly explored without substitution (i.e., R=H) or lead selectively to the formation of products possessing a Z ‐configured double bond distal to the hydroxy group when R≠H, and hence display limited product scope; iii) transition metal catalyzed hydroalkenylations, of propargylic alcohols using boronic acids, and the reported examples employ only internal propargyl alcohol substrates and exhibit either the opposite or poor regiochemistry; iv) intermolecular enyne metathesis, which displays low/moderate E / Z selectivities; v) one related case of an oxidative Heck reaction (57 % yield; not shown) …”
Section: Figurementioning
confidence: 99%
“…The venerable Suzuki–Miyaura cross-coupling (SMCC) has revolutionized C–C bond formation for synthetic chemistry . Whereas it has been predominantly used for C sp2 –C sp2 cross-coupling, within the past two decades, significant advances have been made for the analogous C sp2 –C sp3 variant using aryl halides and alkylboronates as the coupling partners. , This type of reaction is of particular interest for the pharmaceutical industry, as potential drug candidates with greater sp 3 character are considered to be more drug-like. To accomplish these challenging cross-couplings, many early reports disclose the use of alkylboranes or boronic acids. , More recently, the use of potassium alkyltrifluoroborate salts, ,− ,,,,− alkylboronic esters, ,,,− , and MIDA alkylboronates , has arisen as a popular strategy to circumvent the oxidative liabilities associated with alkylboronic acids or boranes. Despite these developments, a recent benchmarking study of methods for C sp2 –C sp3 cross-coupling employing aryl halides and alkyl nucleophiles as coupling partners revealed that modern B-alkyl SMCC conditions succeeded in obtaining the cross-coupled product 61% of the time for 1° alkylboronates and 20% of the time for 2° alkylboronates, with an overall success rate of only 37% …”
Section: Introductionmentioning
confidence: 99%